PENGARUH MODEL PEMBELAJARAN SAVI (SOMATIC, AUDITORY, VISUALIZATION, INTELLECTUAL) DENGAN MEDIA HIDE DAN SEEK PUZZLE TERHADAP HASIL BELAJAR IPA - Puspitasari, Ana; Purnanto, Arif Wiyat; Hermahayu, Hermahayu (Edukasi Journal, 2018)
This study aims to determine the effect of the SAVI learning model (Somatic, Auditory, Visual, Intellectual) to learning results on grade V students of Rejosari Primary School 3 Bandongan. This research method is pre-experimental desig.ns with one group pretest posttest models. The independent variable of the study is the SAVI learning model with the Hide dan Seek Puzzle (X) media and the dependent variable is the science learning outcomes (Y). The research subjects were 22 fifth grade students of Rejosari 1 Bandongan Public Elementary School. The sampling technique uses saturated sampling or total sampling. Data collected using test questions. Data analysis using paired-sample t-test by SPSS for Windows version 23.0. The results of this research shows SAVI learning model had a positive effect to student learning outcomes in science subjects. This is evidenced from the results of the paired-sample t-test analysis with a significance value of 0,000 <0,05. Based on the results of the analysis and discussion, the average value of the overall posttest of respondents after being given treatment increased from the average value of pretest 61.82 to 83.77. The results of this reserch can be concluded that the use of SAVI learning model with the Hide dan Seek Puzzle media has a significant effect on the improvement of science learning outcomes.